Indonesia hari esok - Rif'an, Ali. (Mantrijeron, Yogyakarta : Buku Litera ; Purwokerto : Obsesi Press, 2012)
On social, economic, and political conditions in Indonesia; collection of articles.
Includes bibliographical references.
Keywords: Indonesia -- Politics and government -- 1998-; Indonesia -- Social conditions; Indonesia -- Economic conditions -- 1997-